TINJAUAN YURIDIS PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PEMALSUAN SERTIFIKAT VAKSIN COVID-19 - Rani Nur Isnaini (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The development of the increasing number of positive cases of the Covid-19 virus in various regions has had an impact on several sectors. To prevent the spread of this virus, a vaccination policy has been established by the Government. The position of the covid-19 vaccination is one of the efforts to make a person less susceptible to contracting the covid virus while also prioritizing health protocols. It becomes a problem if the proof of vaccination has been carried out using a writing or certificate that can be misused by other parties by means of forgery. The formulation of the problem proposed by the author is what is the legal basis that can be applied to perpetrators of counterfeiting covid-19 vaccine certificates and what are the forms of prevention against counterfeiting of covid-19 vaccine certificates. The research conducted by the author uses normative legal research using a statutory approach and a case approach. The results of the discussion are the legal basis that can be applied by law enforcement to the perpetrators of the crime of counterfeiting the covid-19 vaccine certificate referring to the provisions of Article 263 paragraph (1) of the Criminal Code while the form of prevention of the crime of counterfeiting the covid-19 vaccine certificate is by preventive and repressive prevention using law enforcement